The Influence Of Work Discipline And Work Environment On The Work Productivity Of Employees In The Hikmah Crackers Factory - Shella Apriani; Suci Putri Lestari; Kusuma Agdhi Rahwana (Journal of Indonesian Management, 2023)
This study aims to find out how Work Discipline and Work Environment affect the Work Productivity of Hikmah cracker factory employees. The research method used in this study is a quantitative research method with a survey approach. The sampling technique used was saturated sampling and 45 respondents were taken as samples. The analytical tool used is the multiple regression equation. The results of the study show that work discipline and work environment simultaneously have a significant influence on employee productivity. Work Discipline partially does not have a significant effect on Employee Productivity. Work environment partially has a significant influence on Employee Productivity